Electrical Conduction in Solid Polymer Electrolytes : A Formula for The Entire Range of Temperatures - Mikrajuddin Mikrajuddin (Indonesian Journal of Physics, 2003)
The experimentally observed temperature dependence of electrical conduction in polymer electrolytes is normally described with two separated equations: an Arrhenius-type relation for relatively low temperatures and a Vogel-Tamman-Fulcher (VTF)-type relation for relatively high temperatures. A single formula, which is valid for the entire range of temperatures, is developed for describing the temperature dependence of electrical conduction in solid polymer electrolytes.